2007
DOI: 10.1016/j.phytochem.2006.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Administering cultured Taxus cells with early precursors reveals bifurcations in the taxoid biosynthetic pathway

Abstract: Feeding studies with Taxus suspension cells employing labeled 5α-hydroxytaxadiene and 5α,10β-dihydroxytaxadiene, and the corresponding 5α-acetate esters, demonstrated that acetylation at C5 of the monool precursor promotes the formation of 14β-hydroxy taxoids, such as taxuyunnanine C, at the expense of 13α-hydroxy taxoids, including Taxol and its congeners, but that the major bifurcation in taxoid biosynthesis, toward 13α-or 14β-hydroxy taxoids, occurs after 10β-hydroxylation of the taxane core.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Similarly, 26 unique sequences with increased transcript changes in T. × media were also up-regulated in T. cuspidata , which contained 29 genes. These include TBT in paclitaxel biosynthesis [28], 1-aminocyclopropane-1-carboxylate oxidase ( ACO ) in ethylene biosynthesis [22], 12-oxophytodienoate reductase possible in jasmonate biosynthesis [29], cationic peroxidase in pathogen incompatible interaction [30], Chalcone synthases involve in phenylpropanoid biosynthesis which is inducible by pathogens [31], and taxane 14b-hydroxylase participating in the bifurcation in paclitaxel biosynthesis [32]. Notably several genes between the different studies were identified as having opposite transcript changes in response to elicitation with MeJA: 15 genes (include one of two ACC oxidases) in T. × media with lower transcript levels were up-regulated in T. cuspidata ,while 7 genes(e.g., dihydroflavonol-4-reductase in anthocyanin biosynthesis [33]) in T. × media with increased transcript levels were identified as down-regulated in T. cuspidata .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, 26 unique sequences with increased transcript changes in T. × media were also up-regulated in T. cuspidata , which contained 29 genes. These include TBT in paclitaxel biosynthesis [28], 1-aminocyclopropane-1-carboxylate oxidase ( ACO ) in ethylene biosynthesis [22], 12-oxophytodienoate reductase possible in jasmonate biosynthesis [29], cationic peroxidase in pathogen incompatible interaction [30], Chalcone synthases involve in phenylpropanoid biosynthesis which is inducible by pathogens [31], and taxane 14b-hydroxylase participating in the bifurcation in paclitaxel biosynthesis [32]. Notably several genes between the different studies were identified as having opposite transcript changes in response to elicitation with MeJA: 15 genes (include one of two ACC oxidases) in T. × media with lower transcript levels were up-regulated in T. cuspidata ,while 7 genes(e.g., dihydroflavonol-4-reductase in anthocyanin biosynthesis [33]) in T. × media with increased transcript levels were identified as down-regulated in T. cuspidata .…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the proportion of the TAX group suggests that MJ‐induction could enhance one‐step or multiple‐step functionalization towards taxol biosynthetic pathways. TC and its derivatives (YN, TPT, TIBT, and TMBT) are unlikely to reside on the route to taxol because of inappropriate acylation patterns on the taxane ring system . Thus, the biosynthetic pathway of MAT is an important bypass to taxol.…”
Section: Resultsmentioning
confidence: 99%
“…The results from both the selected gene expression levels and PCA showed that the genes of OHX1, T10βH, and TαH contribute main variables to the samples induced by MJ, whereas T10βH and TαH seem to be responsible for the hydroxylation at C‐10 and C‐13 of the taxol (taxane) core. Ketchum reported that C‐13 hydroxyl taxanes are easier to generate when the taxanes bear the hydroxyl group at C‐10. Moreover, the variation in B‐III content is the most significant among the identified taxanes after MJ‐induction (Figures and ), correlating well with the variations in the above genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…134 Rather, there is a softening of substrate specificity among the P450 enzymes that are each designed to oxygenate the taxoid core at a specific position. The net result, is that each oxygenated product, can function as a substrate of altering efficiency, for each P450 resulting in a complex matrix of oxygenated polyols, many of which finding their way all the way to baccatin III and taxol.…”
Section: Introductionmentioning
confidence: 99%